Numerical simulation of flow pattern and heat transfer mechanism from a heated cylinder in cross flow - Abang Ma'aruf, Abang Bussri (2009)
Theory of lattice Boltzmann method is introduced to simulate a fluid flow numerically. The lattice Boltzmann method has found to be useful in many application involving interfacial dynamics and complex boundaries. First, the introduction of this report is described the objective of the project. This project objective is to study flow pattern and heat transfer mechanism from a heated cylinder in cross flow. The problem statement is explained in further detailed. The problem is solving using the lattice Boltzmann method theory and some flow simulation. This background of the project is related to the lattice Boltzmann method equation that is involving the Navier-Stoke equation, the governing equation and Bhatnagar-Gross-Krook (BGK) approximation. The literature review explains and described further detail about the lattice Boltzmann method. The methodology discusses about the simulation of the isothermal and thermal of the lattice Boltzmann and how to implement mathematical equation into FORTRAN programming language. The isothermal flow includes the Poiseuille and flow past a cylinder in cross flow. The thermal flow includes the flow past a heated cylinder in cross flow. The isothermal and thermal of lattice Boltzmann equation have been derived from the Boltzmann equation by discretization in both time and phase space. The result obtained by numerical simulation, compared to analytical solution.